A short history of Arabidopsis thaliana (L.) Heynh. Columbia-0 - Somssich,Marc (PeerJ Preprints, 2018)
75 Years ago Arabidopsis thaliana was first suggested as a Model Plant – But how did Arabidopsis Col-0 become the standard natural accession? This is a short history of Arabidopsis thaliana (L.) Heynh. Columbia-0.
Keywords: Arabidopsis thaliana; Columbia-0; Friedrich Laibach; György Rédei; Plant Science History